Calibration and the volatility of labor: A cautionary note - Kevin D. Salyer (University of California, Department of Economics, 2001)
A key parameter in real business cycle models is the weight on the utility of leisure. Typically this parameter is chosen so that the steady-state level of work activity matches the corresponding measure in the data, i.e. the amount of time workers spend in market activity. While the calibration of this parameter is often highlighted in business cycle research, this paper demonstrates that this parameter has no influence on equilibrium characteristics of the Hansen (1985) indivisible labor model, when solved using traditional methods. Hence, the functional form of utility rather than the parameterization of utility is the critical factor.
Keywords: E32; C68; 330; calibration; real business cycles; Real Business Cycle; Modellierung; Theorie